Research on classroom actions to increase learning hours to improve learning outcomes in software as a service subject - Kurniawan, Prawidana; Elmunsyah, Hakkun; Umami, Aktia Arigiana (PT. Pena Produktif Kreatif, 2025)
The addition of study hours is based on the issue that students do not have the tools for independent study, such as laptops. This lack of resources prevents them from practicing programming independently at home, which can lead to a decreased interest in the learning process in the Software as a Service (SaaS) subject. This issue also impacts the achievement of learning objectives. The problems were identified through non-diagnostic and diagnostic assessments related to prior knowledge, conducted via questionnaires. The goal of adding study hours outside of school time is to provide a more effective learning process, directly impacting the faster achievement of learning objectives as per the targets set. The benefits of the additional study hours include students gaining access to computer lab facilities, allowing them to work on projects independently. The extended study hours also provide students with opportunities to ask questions about programming errors or difficulties they encounter in the learning process, particularly in the SaaS subject. The methods used include questionnaires and classroom observations in class XI SIJA I at SMK6 Malang. The selected population consisted of 36 students. The results indicated that the addition of study hours impacted the faster completion of learning objectives. Before the implementation, two learning objectives were completed in three weeks, but with the addition of study hours, 13 learning objectives were completed within 3 weeks.